Penyelesaian Kredit Dengan Jaminan Fidusia Yang Objeknya Dialihkan Oleh Debitur - Fadel Afandi (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This study aims to determine the position of the object of the fiduciary guarantee transferred by the debtor based on the agreement with PT. Pegadaian and to determine the efforts to settle the credit transferred by the debtor. This research was conducted at PT. Pegadaian Pasar Butung Makassar and used the Normative-Empirical research type method. The approach is carried out with literature in reality based on interviews and documentation. The results of the study indicate that to determine the legal position of the object of the fiduciary guarantee transferred by the debtor, registration is required. PT. Pegadaian does not register a fiduciary guarantee in its entirety with consideration of costs, so that the legal position of the object of the fiduciary guarantee has a legal weakness in the sense of lack of legal certainty for creditors, because the debtor has violated the provisions of Article 23 paragraph (2). In addition, to settle loans with fiduciary guarantees whose objects are transferred by the debtor, PT. Pegadaian takes a negotiation method with the debtor and the third party who receives the transfer of the object of the fiduciary guarantee, namely by replacing the object of the collateral transferred to the third party with the object belonging to the debtor whose value is equivalent to the object of the guarantee that has been transferred, because PT. Pegadaian has material rights over the object of collateral.